Individual resilience in a volatile work environment - Ong, Isabel; Kou, Chia-Yu (Springer, 2023)
This chapter is set out to understand the way in which individuals build and maintain their resilience when facing a volatile work environment. We studied this question qualitatively in an S&P 500 company where the company faced major business changes during a time when employees faced work-related restrictions. We described practices that individuals do to maintain or inhibit their psychological resilience. Interestingly, we found that individuals were able to adopt positive framing of the situation across tenure, seniority levels, and involvement in the business change. We also found that the inhibitor for individuals to reframe their situation was related to being unable to rest. Increased working hours and a lack of work-life boundaries inhibited individuals’ pathways to resilience. Building on the findings, the chapter will conclude with managerial implications. First, the findings highlight that both direct managers and senior managers play an important role in shaping individuals’ meaning-making processes, and their narratives could encourage subordinates to demonstrate optimism around the challenge. Second, organizations can consider interventions such as instituting long and short breaks, and mindfulness training to mitigate the negative impact from lack of rest.
Keywords: Resilience; Volatile context; Uncertainty; Organizational change; Stress